1996
DOI: 10.1136/jcp.49.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Observer variability in histopathological reporting of non-small cell lung carcinoma on bronchial biopsy specimens.

Abstract: Aims-To evaluate the ability of histopathologists to sub-classify non-small cell lung carcinomas on bronchial biopsy material using the current World Health Organisation (WHO) classification. Methods-Twelve histopathologists each reviewed 100 randomly selected bronchial biopsy specimens which had originally been reported as showing non-small cell lung carcinoma. For each case, two sections were circulated, one stained by haematoxylin and eosin and the other by a standard method for mucin (alcian blue/ periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…However, agreement is lower for determination of NSCLC subtype. The agreement seen for both determination of NSCLC subtype (k50.278, 95% CI 0.075-0.481) and distinction of SCLC from NSCLC is consistent with agreement previously reported for bronchial biopsy specimens [8,22,23].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…However, agreement is lower for determination of NSCLC subtype. The agreement seen for both determination of NSCLC subtype (k50.278, 95% CI 0.075-0.481) and distinction of SCLC from NSCLC is consistent with agreement previously reported for bronchial biopsy specimens [8,22,23].…”
Section: Discussionsupporting
confidence: 78%
“…Interobserver agreement and confidence may differ based on the experience of reporting pathologists. While agreement may be higher between experienced pulmonary pathologists, interobserver agreement noted in this study is comparable to that reported by BURNETT et al [8] among pathologists not experienced in evaluation of lung pathology. This suggests that our findings may accurately represent clinical practice in the majority of centres worldwide where anatomical pathologists report on EBUS-TBNA specimens rather than specialist pulmonary pathologists.…”
Section: Limitationssupporting
confidence: 75%
See 3 more Smart Citations